Study of alleles of the second complement component (C2) on Canadian HLA haplotypes. - Marshall, W; Barnard, J; Churchill, D; Farid, N; Grandy, R; Larsen, B; Payne, R; Skanes, V; Ebers, G; Paty, D (1984)
Typing for genetic variation in the second complement component C2 was performed on sera from HLA haplotyped Canadian families. Part of the data has been studied and analysed as a population; in addition there is a further random collection of haplotypes bearing the C2*2 allele. In the population data there were 444 separate haplotypes from unrelated parents or other founders: 4.7% of the haplotypes carried the uncommon allele C2*2; one haplotype carried the rare C2*3. Study of C2 2-1 heterozygotes in the population data revealed 59 haplotypes which carried the common C2*1 allele and one which carried a deficiency allele C2*0. The remaining haplotypes carried either C2*1 or else an undetectable C2*0 allele. In the entire data there were 281 meioses informative for C2. The only recombinant between HLA-B and C2 showed the C2 locus to be on the DR side of the B locus. Strong allelic association between C2 *2 and Bw22 and less strong association between C2 *2 and B15 suggested the possibility of two ancestral C2 mutants. Examination of other markers on these and subsequently collected haplotypes do not conflict with this idea since the B15 haplotypes mostly carry C4A *4, C4B *2 whilst the Bw22 haplotypes mostly carry C4A *4, C4B *4. The alternative idea, that there was one original mutant which crossed over from a B15 to a Bw22 haplotype or vice versa is not excluded, however. Since approximate equilibrium has been reached between Bw22 and the HLA-A locus alleles on these C2 *2 bearing haplotypes, we conclude that this mutation is at least 5000 years old. Other haplotypes carrying C2 *2 are assumed to be ancestral recombinants; if this is true, the C2 locus map position between HLA-B and HLA-DR is confirmed. Study of C2 mutation may provide a model for understanding the genetics of some disease susceptibility genes in the HLA region.